Pure cartilaginous choristoma on the ventral surface of tongue: A double rarity (Indian Journal of Case Reports, 2019)
Choristomas are tumor like mass that are aggregates of microscopically normal tissue in an abnormal location. Commonly reported choristomas are of Osseous, Cartilaginous, Glandular and Glial types. The oral cavity is an unusual site of presentation where the most common site is dorsum of the tongue. Ventral aspect is an extremely rare site with only four cases reported till date. We report here a case of a 24-year-old male who presented with a small swelling on the ventral surface of the tongue. The histopathological examination revealed features of a well-circumscribed mass composed of exclusively mature cartilage encased within a dense fibrous connective tissue. The case is presented for its double rarity of site which is a ventral surface of the tongue and the histopathology which revealed a pure form of cartilaginous choristoma.